How do you simplify the expression #(4m^4)/(-6m^-2n^5)*(3n^-1)/m^-2# using the properties?

1 Answer
Nov 9, 2017

Answer:

#=-(2m^8)/(n^6)#

Explanation:

Some of the laws of indices state:

#x^m xx x^n = x^(m+n)#

#x^-m = 1/x^m" "and" "1/x^-m = x^m#

This means that negative indices can be changed to positive indices.

#(4m^4)/(-6m^-2n^5) xx (3n^-1)/(m^-2)#

#= (4m^4m^2)/(-6n^5) xx (3m^2)/(n)" "larr#all positive indices

#= (cancel4^2m^4m^2)/(-cancel6^cancel2n^5) xx (cancel3m^2)/(n)#

#=-(2m^8)/(n^6)#